Modeling The Fate of Sumatran Elephants in Bukit Tigapuluh Indonesia: Research Needs & Implications for Population Management - Alexander Markus Moßbrucker; Muhammad Ali Imron; Satyawan Pudyatmoko; Peter-Hinrich Pratje; Sumardi Sumardi (Fakultas Kehutanan Universitas Gadjah Mada, 2016)
The critically endangered Sumatran elephant persists in mainly small and isolated populations that may require intensive management to be viable in the long term. Population Viability Analysis (PVA) provides the opportunity to evaluate conservation strategies and objectives prior to implementation, which can be very valuable for site managers by supporting their decision making process. This study applies PVA to a local population of Sumatran elephants roaming the Bukit Tigapuluh landscape, Sumatra, with the main goal to explore the impact of pre-selected conservation measures and population scenarios on both population growth rate and extinction probability. Sensitivity testing revealed considerable parameter uncertainties that should be addressed by targeted research projects in order to improve the predictive power of the baseline population model. Given that further habitat destruction can be prevented, containing illegal killings appears to be of highest priority among the tested conservation measures and represents a mandatory pre-condition for activities addressing inbreeding depression such as elephant translocation or the establishment of a conservation corridor.Keywords: Elephas maximus sumatranus; population viability analysis (PVA); Asian elephant; elephant conservation; Vortex Pemodelan Kelestarian dari Gajah Sumatera di Bukit Tigapuluh Indonesia: Kebutuhan Penelitian dan Implikasi untuk Manajemen PopulasiAbstractGajah Sumatera yang berstatus kritis sebagian besar bertahan dalam populasi kecil dan terisolasi membutuhkan pengelolaan intensif agar dapat tetap lestari dalam jangka panjang. Analisis Viabilitas Populasi (Population Viability Analysis, PVA) berpeluang untuk digunakan sebagai sarana evaluasi atas tujuan dan strategi konservasi yang disusun sebelum implementasi, yang akan sangat bermanfaat bagi pengelola kawasan guna mendukung pengambilan keputusan. Studi ini menggunakan PVA pada populasi lokal gajah Sumatera yang menjelajahi lanskap Bukit Tigapuluh, Sumatera, dengan tujuan utama mengeksplorasi dampak atas skenario upaya konservasi dan populasi terpilih terhadap laju pertumbuhan populasi dan probabilitas kepunahan. Uji sensitivitas menunjukkan adanya ketidakpastian atas sejumlah parameter pokok yang seharusnya diteliti untuk meningkatkan kekuatan prediksi atas baseline model populasi. Mengingat kerusakan habitat yang lebih parah dapat dicegah, untuk itu upaya penangkalan pembunuhan ilegal merupakan prioritas tertinggi di antara upaya-upaya konservasi yang sudah diuji dan menjadi prasyarat wajib untuk menjawab masalah kemungkinan dampak perkawinan sedarah (inbreeding depression) seperti translokasi gajah atau membangun koridor konservasi.